PENGARUH GUIDED DISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS BERDASARKAN DISPOSISI SISWA - Siti Nurholiza; Arnida Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of Guided Discovery Learning on mathematical creative thinking skills based on students’ dispositions. This is an experimental study with a factorial experimental design. The population of this study consists of all eighth-grade students at MTsS Pekan Tebih for the 2025/2026 academic year. The sample was selected using cluster random sampling, with Class VIII.B designated as the experimental class and Class VIII.A as the control class. The data analysis technique used was a two-way ANOVA. Based on the results of the data analysis, it can be concluded that: 1) There is a difference in mathematical creative thinking ability between students taught using the Guided Discovery Learning model and those taught using the conventional learning model. 2) There is a difference in mathematical creative thinking ability among students with high, moderate, and low mathematical dispositions. 3) There is no interaction between the Guided Discovery Learning model and mathematical disposition on students’ mathematical creative thinking ability.